On the determination of the D meson width in the nuclear medium with the transparency ratio - Victor Montesinos; Natsumi Ikeno; Eulogio Oset; Miguel Albaladejo; Juan Nieves; Laura Tolos (Physics Letters B)
We have studied the feasibility of the experimental determination of the width of a D meson in a nuclear medium by using the method of the nuclear transparency. The cross section for inclusive production of a D+ in different nuclei is evaluated, taking care of the D+ absorption in the nucleus, or equivalently, the survival probability of the D+ in its way out of the nucleus from the point of production. We use present values of the in medium width of D mesons and calculate ratios of the cross sections for different nuclei to the C12 nucleus as reference. We find ratios of the order of 0.6 for heavy nuclei, a large deviation from unity, which indicates that the method proposed is adequate to measure this relevant magnitude, so far only known theoretically.